PENDAMPINGAN PEMBUATAN KEMASAN SEBAGAI ALAT BRANDING: MENCIPTAKAN IDENTITAS PRODUK YANG KUAT - Wulandari, Chintiya; Sholihah, Zilfatus; Failany, M. Afif; Imamsyah, M. Alim; Utomo, Fajar Nur; Tamyiz, Muchammad (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
Product packaging not only serves as a protector but also as a strategic tool to build a strong identity and brand image. In Gisik Cemandi Village, MSMEs (Micro, Small, and Medium Enterprises) play a vital role in the local economy; however, many MSME owners face challenges in creating a strong product identity. One way to overcome this challenge is by redesigning product packaging as a branding tool. This community service activity aims to analyze how packaging can be utilized to enhance the competitiveness and brand awareness of MSMEs in Gisik Cemandi Village. The methods used include surveys, interviews, packaging redesign, and distributing questionnaires to consumers to gather insights into their expectations regarding packaging design. The results of the study show that many MSME owners in the village have not fully utilized the potential of packaging design. The existing packaging tends to be monotonous and unappealing, while innovative packaging designs can enhance product quality perception and consumer purchase decisions. After conducting counseling and redesigning the packaging, MSME owners gained knowledge about the importance of packaging design in creating a strong product identity and attracting consumers. The new packaging is more informative, appealing, and capable of building a positive brand image. Thus, good packaging design can be an effective branding tool in increasing brand awareness and product competitiveness in a competitive market. It is expected that by applying this strategy, MSMEs in Gisik Cemandi Village will be able to expand their market share and increase their product sales.